Malignant Cutaneous Melanoma: Updates in PET Imaging - Laudicella, Riccardo; Baratto, Lucia; Minutoli, Fabio; Baldari, Sergio; Iagaru, Andrei (Current Radiopharmaceuticals, 2020)
Background: Cutaneous malignant melanoma is a neoplasm whose incidence and mortality are dramatically increasing. 18F-FDG PET/CT gained clinical acceptance over the past 2 decades in the evaluation of several glucose-avid neoplasms, including malignant melanoma, particularly for the assessment for distant metastases, recurrence and response to therapy. Objective: To describe the advancements of nuclear medicine for imaging melanoma with particular attention to 18F-FDG-PET and its current state-of-the-art technical innovations. Methods: A comprehensive search strategy was used based on SCOPUS and PubMed databases. From all studies published in English, we selected the articles that evaluated the technological insights of 18FFDG- PET in the assessment of melanoma. Results: State-of-the-art silicon photomultipliers based detectors (“digital”) PET/CT scanners are nowadays more common, showing technical innovations that may have beneficial implications for patients with melanoma. Steady improvements in detectors design and architecture, as well as the implementation of both software and hardware technology (i.e., TOF, point spread function, etc.), resulted in significant improvements in PET image quality while reducing radiotracer dose and scanning time. Conclusion: Recently introduced digital PET detector technology in PET/CT and PET/MRI yields higher intrinsic system sensitivity compared with the latest generation analog technology, enabling the detection of very small lesions with potential impact on disease outcome.
Keywords: PET/MRI